PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP PENGUNGKAPAN AKUNTANSI SUMBER DAYA MANUSIA - Rahayu, Andarista Puji; Sulistyawati, Ardiani Ika (Solusi, 2019)
ABSTRACT Human resources is an intangible asset and is the most important factor that determines the success of the company . The role of human resources (HR) in the development of the business world that is increasingly rapidly considered very important for any company . Qualified human resources will lead the organization in both comparative advantage and competitive basis and was instrumental in running the company’s operations and optimally executing business strategy .This research aims to determine the effect of company size , size of board of commissioners , the concentration of ownership and status on the disclosure of accounting lisitng human resources . Type of data used in this study is secondary data. Purposive sampling method used in sample selection. The results of this study prove that simultaneously (F est) accounting disclosure index of human resources can be explained by all the variables. While (t test) indicates that the variable board size significantly influence accounting disclosure of human resources . Keywords :human resources accounting disclosure, company size, the concentration of ownership and listing status